THE APPLICATION OF CRIMINAL SANCTIONS AGAINST RESTAURANT OWNERS WHO FACILITATE NON-FASTING MUSLIMS DURING RAMADHAN - Teuku Murhaban (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2018)
The purpose of this writing is to explain why the application is not effective. Criminal Sanctions against violators of qanun No.11 of 2002 concerning the implementation of Islamic Shari'a in the field of Worship, Article 10 paragraph (1) jo Article 22 paragraph (1). Based on the research results, it is known that the ineffective application of criminal sanctions in Article 10 paragraph (1) jo Article 22 paragraph (1) of qanun No. 11 of 2002 concerning the implementation of Islamic Shari'a is due to the limited members of Wilayatul al-Hisbah then the distance travelled by the security team during operations to patrol is not easy to reach because of the vast area of Aceh Besar district and the low human resources of Wilayatul al-Hisbah members and the community about the implementation of this qanun and there is no cooperation of all elements. From the explanation that has been listed above, it can be concluded that the application of criminal sanctions against violators of qanun No. 11 of 2002 concerning the implementation of Islamic Shari'a Article 10 paragraph (1) jo Article 22 paragraph (1) does not run effectively in Aceh Besar Jantho City.